Exciting Times - Kathy Crooks (Rural Nurse Organization; Binghamton University, 2004)
The past year has been an exciting time for nurses working in rural and remote parts of Canada. While 95 percent of this immense country is considered to be rural or remote, only 18 percent of all nurses in Canada are employed in these areas. Because of distance and lack of technology in some areas, until very recently it has been impossible for this small number of nurses to organize and band together to advance the cause of rural nursing in Canada. This all changed at the Canadian Nurses Association Biennium in St. John's Newfoundland in June, 2004. At that time, a group of about 30 nurses from across Canada with an interest in rural/remote nursing met to discuss the organization of the Canadian Association of Rural and Remote Nurses (CARRN). CARRN is in the process of electing its first slate of officers. The emergence of an organization such as CARRN is a monumental undertaking. Its inception is the result of the hard work of Dr. Dana Edge and Meg McDonoagh of the University of Calgary, as well as Barb Shellian, a former president of the Alberta Association of Registered Nurses. These three individuals, along with Dr. Elizabeth Thomlinson, met in Binghamton, New York, for the Third International Congress. From that meeting, the idea for CAARN was born.